A hundred years of consciousness: “a long training in absurdity” - Strawson, Galen (Estudios de Filosofía, 2019)
There occurred in the twentieth century the most remarkable episode in the history of human thought. A number of thinkers denied the existence of something we know with certainty to exist: consciousness, conscious experience. Others held back from the Denial, as we may call it, but claimed that it might be true —a claim no less remarkable than the Denial. This paper documents some aspects of this episode, with particular reference to two things. First, the development of two views which are forms of the Denial —philosophical behaviourism, and functionalism considered as a doctrine in the philosophy of mind— from a view that does not in any way involve the Denial: psychological methodological behaviourism. Second, the rise of a way of understanding naturalism —materialist or physicalist naturalism— that wrongly takes naturalism to entail the Denial.